Термолюмiнесценцiя квантових точок кремнiю в моделi двi пастки–один центр рекомбiнацiї - Gemechu, N.; Senbeta, T.; Mesfin, B.; Mal’nev, V. N. (Publishing house "Academperiodika", 2018)
A model of the first and general order kinetics describing the thermoluminescence (TL) from silicon quantum dots consisting of two active electron trap levels and one recombination center is proposed. The two trap levels are located at different trap depths beneath the edge of the conduction band. The rate equations corresponding to each trap level allow us to numerically simulate the variation of the concentration of electrons in the two traps and the TL intensity as a function of the temperature for quantum dots 2–8 nm in diameter. It is shown that the intensity increases with decreasing in the dot size, indicating that the quantum confinement effect enhances the radiative recombination rate. The two peaks of the intensity correspond to the two different active electron trap levels. With an increase in the dot size, the peaks of the intensity corresponding to the deepest trap shift to the high temperature region. The variation of the concentration of electrons in the traps is given, and this result bridges the experimental gap, where the TL glow curves are generated, and the variation of the concentration of electrons in traps is unknown.